2020
DOI: 10.3389/fimmu.2020.01026
|View full text |Cite
|
Sign up to set email alerts
|

Th9 Cell Differentiation and Its Dual Effects in Tumor Development

Abstract: With the improved understanding of the molecular pathogenesis and characteristics of cancers, the critical role of the immune system in preventing tumor development has been widely accepted. The understanding of the relationship between the immune system and cancer progression is constantly evolving, from the cancer immunosurveillance hypothesis to immunoediting theory and the delicate balance in the tumor microenvironment. Currently, immunotherapy is regarded as a promising strategy against cancers. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 124 publications
1
64
0
Order By: Relevance
“…The function of IL9 in tumor immunity is controversial [52][53][54]. It has been generally suggested that IL9 may inhibit the growth of solid tumors by activating the innate or adaptive immune response [55,56], while as a lymphocyte growth factor it may promote progression of hematological malignancies [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of IL9 in tumor immunity is controversial [52][53][54]. It has been generally suggested that IL9 may inhibit the growth of solid tumors by activating the innate or adaptive immune response [55,56], while as a lymphocyte growth factor it may promote progression of hematological malignancies [10,12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been generally suggested that IL9 may inhibit the growth of solid tumors by activating the innate or adaptive immune response [55,56], while as a lymphocyte growth factor it may promote progression of hematological malignancies [10,12]. However, since IL9 has also been reported to promote proliferation of multiple solid tumor models (like pancreatic cancer, lung cancer and colitis associated cancer) [57][58][59], its anti-cancer activity may be context and tumor type specific [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The function of IL9 in tumor immunity is controversial. 5355 It has been generally suggested that IL9 may inhibit the growth of solid tumors by activating the innate or adaptive immune response, 56,57 while as a lymphocyte growth factor it may promote progression of hematological malignancies. 10,12 However, since IL9 has also been reported to promote proliferation of multiple solid tumor models (like pancreatic cancer, lung cancer, and colitis associated cancer), 5860 its anti-cancer activity may be context and tumor type specific.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 However, since IL9 has also been reported to promote proliferation of multiple solid tumor models (like pancreatic cancer, lung cancer, and colitis associated cancer), 5860 its anti-cancer activity may be context and tumor type specific. 5355…”
Section: Discussionmentioning
confidence: 99%
“…IL-9 has been considered a predominant signature cytokine of Th9 cells and plays critical roles in the allergic and antitumor immune responses mediated by Th9 cells [38,39]. Furthermore, mouse and human Th9 cells also secret other cytokines such as IL-21, IL-10, IL-17, and IL-22, which orchestrate the immune responses in cancer and allergic asthma [30,[40][41][42].…”
Section: Characterization Of the Cell Subsetsmentioning
confidence: 99%